2013
DOI: 10.1080/02687038.2012.757760
|View full text |Cite
|
Sign up to set email alerts
|

Formulaic language in Alzheimer's disease

Abstract: Background Studies of productive language in Alzheimer’s disease (AD) have focused on formal testing of syntax and semantics but have directed less attention to naturalistic discourse and formulaic language. Clinical observations suggest that individuals with AD retain the ability to produce formulaic language long after other cognitive abilities have deteriorated. Aims This study quantifies production of formulaic expressions in the spontaneous speech of individuals with AD. Persons with early- and late-ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
3
25
0
4
Order By: Relevance
“…As subcortical structures have been shown to be involved in procedural memory for syntax production (Ullman, 2008; Zanini et al, 2004), recitation speech as a task may also be procedural, driven by subcortical neural substrates controlling automatic, overlearned motor sequences. Similar to findings of formulaic language (see Bridges & Van Lancker Sidtis, 2013; Rogers et al, 2009 for discussion of formulaic language in Alzheimer's disease and Parkinson's disease), successful recitation speech is also associated with an intact subcortex, as deficits are observed with severe subcortical dysfunction (in the participants with DBS turned OFF). Overall, these findings provide support for the dual process model of language production involving a subcortical-right-hemisphere circuit in addition to the left-hemisphere (Van Lancker Sidtis, 2004, 2006, 2012; Wray & Perkins, 2000).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…As subcortical structures have been shown to be involved in procedural memory for syntax production (Ullman, 2008; Zanini et al, 2004), recitation speech as a task may also be procedural, driven by subcortical neural substrates controlling automatic, overlearned motor sequences. Similar to findings of formulaic language (see Bridges & Van Lancker Sidtis, 2013; Rogers et al, 2009 for discussion of formulaic language in Alzheimer's disease and Parkinson's disease), successful recitation speech is also associated with an intact subcortex, as deficits are observed with severe subcortical dysfunction (in the participants with DBS turned OFF). Overall, these findings provide support for the dual process model of language production involving a subcortical-right-hemisphere circuit in addition to the left-hemisphere (Van Lancker Sidtis, 2004, 2006, 2012; Wray & Perkins, 2000).…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, Sidtis et al (2009) found reduced incidence of formulaic language in the spontaneous speech of individuals who have had subcortical strokes when compared to healthy adults. Findings from studies of the speech of individuals with Alzheimer's disease show relative preservation of formulaic language even when novel language production deteriorates due to cortical degeneration (Bridges & Van Lancker Sidtis, 2013), providing evidence that intact subcortical structures may be involved in the production of this language form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Producing more empty phrases and conjunctions (Nicholas, Obler, Albert, & Helm-Estabrooks, 1985). Indefinite pronouns and general names occur as substitutions for the target word in everyday conversations, according to the well-known peculiarity of the AD patients' speech (Bridges & Van Lancker Sidtis, 2013). Our patient used indefinite pronouns in spontaneous speech, sometimes pretending to generate a figure of speech, making an attempt to mask her word recollecting failures.…”
mentioning
confidence: 99%
“…The influence of poor semantic processing and weak executive functioning on the verbal communication in general. Individuals with AD overuse cliché (Bridges & Van Lancker Sidtis, 2013) because a cliché penetrates into the speech program automatically as a filler of a syntactic position. The increase of the associations in naming tests and spontaneous speech reflects the poor semantics, insofar as associations replace semantic relations and accuracy of the lexical selection.…”
mentioning
confidence: 99%